Analisis Strategi Pemasaran Pada Usaha Mikro Kecil dan Menengah (UMKM) Pada Era Digital di Kota Bandung - Iston Dwija Utama (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2019)
The emergence of technology and high business competition makes Small Medium Sized (SMEs) have a strong and clear marketing strategy to compete with their competitors. The aim of this research to analyze the marketing strategy implementation in SMEs to compete in digital era. Research method of this research conduct with qualitative approach by using structured interview with the owners or top level management of SMEs with numbers of sample are 31 respondents. Result of this research showed that culinary, fashion, and tour and travel industries implement the added value and differentiation strategy for their products and services, they also give competitive price strategy. Different for trading industry, they tend to use the pricing strategy to compete in market and select the niche market to develop their target market. Technology implementation also well-used by culinary, fashion, and tour and travel industries through website and social media to engaged and communicate with their customers and audiences